Effect of level combinations of nitrogen and phosphorus fertilizers on growth and yield of faba bean (Vicia faba L.) in a calcareous soil from Sulaimani province - Rasul1, Ghafoor Ahmed Mam (Sulaimani Journal for Pure and Applied Sciences, 2018)
A field experiment was carried out in the Research Farm of the College of Agricultural Sciences, University of Sulaimani, Kurdistan Region of Iraq, during the winter season of 2014 to evaluate the effect of levels combinations of nitrogen and phosphorus fertilization on growth and yield of faba bean( Vicia faba L.). The experiment was arranged in arandomized completeblock design (RCBD) with three replicates. The results indicate that the nitrogen and phosphorus fertilizers had no significant effect on most studied growth characteristics of faba bean except for the plant height. The greatest plant height was observed from the application of 78 kg N ha-1and 200 kg P2O5 ha-1(T3) fertilizers. Chlorophyll content index (CCI) was not affected by the nitrogen and phosphorus fertilizer application. The highest chlorophyll content index was found under the application of 98 kg N ha-1 and 250 kg P2O5 ha-1 (T4) to the soil. Statistical analysis revealed that nitrogen and phosphorus fertilizers had no significant effect on the value of harvest index, the highest value of harvest index 43.93% was shown from the application of 98 kg N ha-1 and 250 kg P2O5 ha-1 (T4). Phosphorus application had no significant effect on phosphorus use efficiency (PUE). The lower phosphorus use efficiency (PUE) was observed at highest P rates application, the maximum PUE (86.40) was observed from the combination of 58 kg N ha-1 with 150 P2O2 kg ha-1 (T2), and it decreased at higher P rate application to (61.22).
Keywords: Faba bean; Nitrogen; and Phosphorus fertilizers